Stiffness evaluation of the leading edge of the dragonfly wing via laser vibrometer - Chen, Y. H. (2013)
The material property of the leading edge vein (LEV) of the dragonfly wing is investigated. A new vibration method is developed using a laser vibrometer and mini-shaker. The natural frequency of a cantilevered LEV is determined via lateral oscillation. As a result, the elastic modulus of a LEV sample from a dragonfly wing is found to be in the range of the elastic hydrocarbon polymer, while a dead dragonfly is similar to low density polyethylene. The loss of water contents in the veins increases the stiffness of the LEV by approximately 20 times.